Trading in Local Energy Markets and Energy Communities Concepts, Structures and Technologies - Shafie-khah, Miadreza; Gazafroudi, Amin Shokri (Lecture Notes in Energy, 2023)
VI, 261 p. 71 illus., 51 illus. in color.